Culinary Education: Evaluating Stake’s Countenance Model in Case-Based Learning - Yuni Aulia; Riyadi; Rina Febriana (PT. Anagata Sembagi Education, 2025)
This study examines the effectiveness of case-based learning in a culinary education program through the lens of Stake’s Countenance Model of evaluation. The research seeks to identify how this evaluation framework can illuminate critical dimensions of teaching and learning, ultimately guiding improvements in curricular design and instructional practices.